477 Socioeconomic status, demographic and personal factors, and the eating behaviours of civil service employees: a cross-sectional study. (24th April 2018) - Grant, Judith; Houdmont, Jonathan; Munir, Fehmidah; Kerr, Robert; Adley, Ken
Abstract : Introduction: This study concerns the relationship between socioeconomic status (SES) and eating behaviours in working populations. Much research exists on this topic in a community setting, however more research is needed in a workplace setting to help inform the targeting of interventions to improve employee health. Methods: The study was conducted in 2014 using a single self-report anonymous questionnaire. The variables of interest in this study were age, gender and number of dependents, three measures of SES (education, income and job type), Body Mass Index (BMI), and diet. Two items, 'how often do you eat past the point of feeling full?' and 'to what extent does the cost of food influence what you buy?' were introduced into the survey in response to a literature review. Hierarchical linear regression analyses were conducted to examine the variance in eating behaviours. Result: A 20% response rate was achieved with 6206 responses. All three SES variables, in addition to age, number of dependents and BMI accounted for 9% of the variance in the cost of food influencing purchase behaviours; age, gender and BMI explained 7% of the variance in eating past the point of feeling full; gender, BMI and all SES variables explained 1% of the adjusted variance in vegetable consumption; age, gender and BMI explained 2% of the variance in fruit consumption and age, gender, BMI, education and salary band explained 5% of the variance in consumption of a healthy well-balanced diet. Discussion: The findings demonstrate the importance of socioeconomic status in eating behaviours and suggest that demographics also play a significant role in influencing employee eating behaviours. This raises interesting questions as to the feasibility of targeting healthy eating interventions at work on the basis age or BMI.